기업가의 통찰력이 중소기업 지속가능경영에 미치는 영향에 관한 연구 - 김원주(Wonju Kim); 양동우(Dongwoo Yang) (대한경영학회지, 2021)
경영예측과 판단이 어려워지고 있는 환경변화 속에서 기업이 생존률을 높이고, 기업발전의 지속 성장을위해서는 기업가의 통찰력을 이해할 필요가 있다. 기업가의 통찰력은 경험, 직관 등 여러 요소들의 상호작용을거쳐 기업경영 의사결정에 영향을 미침으로써 기업을 ‘지속가능한 기업’으로 성장시키는 중요한 역할을 한다. 통찰력은 기업가 혼자의 노력을 통해서도 가능하지만 구성원과의 사회적 상호관계내지 연대를 통해 성장하고구체화되는 과정을 거친다. 통찰력이 폐쇄적 환경보다 개방적 환경에서 더 적합한 생태토양을 기반으로 하여성장함을 의미한다. 이와 관련하여 통찰력 구현을 위한 주위 환경 요소들 가운데 기업 내 집단 간 태도인사회지배지향성에 관한 내용을 살펴볼 필요가 있다. 사회지배 지향성은 사회 내 특정 집단이 다른 집단에대해 지배력을 행사하거나 불평등을 지지하는 성향으로 사회지배성향이 높은 기업가는 그렇지 않은기업가보다 온전한 통찰력 형성 내지 구현이 어려울 것이다. 아울러 종속변수로써 경제적 책임, 사회적 책임, 환경적 책임을 그 구성요소로 하는 지속가능경영을 제시하였다. 본 연구에서는 통찰력, 사회지배지향성, 지속가능경영의 이론적 고찰을 하고, 이들 상호간의 관계를 다음과같이 실증 분석하였다. 첫째, 통찰력과 사회지배지향성의 관계분석 결과, 통찰력의 전략적 관심, 멘탈시뮬레이션은 사회지배지향성의 사회적 위계성에 유의하였으나, 통찰력의 참여적 의사결정은 사회적위계성에 유의하지 않은 것으로 나타났다. 또한 통찰력의 전략적 관심, 참여적 의사결정이 사회지배지향성의사회적 반평등성에 유의하지 않은 반면, 통찰력의 멘탈시뮬레이션은 사회지배지향성의 사회적 반평등성에유의한 것으로 나타났다. 둘째, 통찰력과 지속가능경영의 관계분석 결과, 통찰력의 참여적 의사결정이지속가능경영에 유의하게 나타났으나, 전략적 관심과 멘탈시뮬레이션은 지속가능경영에 유의하지 않은것으로 나타났다. 셋째, 사회지배지향성과 지속가능경영의 관계분석 결과, 사회적 위계성과 사회적 반평등성은지속가능경영에 유의한 것으로 나타났다. It is necessary to understand the insight of entrepreneurs in order for companies to increase their survival rate and to achieve sustainable growth in corporate development amid changes in the environment in which business prediction and judgment are difficult. Entrepreneur’s insight plays an important role in growing a company into a ‘sustainable company’ by influencing corporate management decision-making through the interaction of various factors such as experience and intuition. Insight is possible through the entrepreneur’s own efforts, but it goes through the process of growing and materializing through social interaction or solidarity with members. It means that insight grows on the basis of ecological soils that are more suitable in an open environment than in a closed environment. In this regard, it is necessary to examine the social domination orientation, which is an attitude between groups within a company, among environmental factors for the realization of insight. Social domination orientation is a tendency in which certain groups in society exercise dominance over other groups or support inequality. In addition, as a dependent variable, sustainability management with economic responsibility, social responsibility, and environmental responsibility as its components was presented. In this study, theoretical considerations of insight, social domination orientation, and sustainable management were conducted, and the relationship between them was empirically analyzed as follows. First, as a result of analyzing the relationship between insight and social domination orientation, strategic interest of insight and mental simulation showed that the social hierarchy of social domination orientation was significant, but participatory decision-making of insight did not have significant significance on social hierarchy. In addition, the strategic interest of insight and participatory decision-making did not show significance in the social anti-equality of the social domination orientation, whereas the mental simulation of the insight was significant in the social anti-equality of the social domination orientation. Second, as a result of analyzing the relationship between insight and sustainability management, it was found that the participatory decision-making of insight was significant in sustainability management, but strategic interest and mental simulation were not significant in sustainability management. Third, as a result of analyzing the relationship between social domination orientation and sustainable management, social hierarchy and social anti-equality were found to be significant in sustainable management. KCI Citation Count: 0